Analisis Kemampuan Pemecahan Masalah dalam Menyelesaikan Soal Cerita pada Materi Operasi Hitung Campuran Kelas II Sekolah Dasar - Dewi Budi Juniati; Ryky Mandar Sary; Filia Prima Artharina (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study was to describe the problem-solving ability in solving math's word problems on mixed arithmetic operations in grade 2 of elementary school level. This research used a qualitative descriptive approach. The subject of this study consisted of 22 students, then 6 students were taken to be interviewed with the criteria: 2 high abilities; 2 moderate abilities; and 2 low abilities. In this study, researchers also used several methods to collect data: tests, interviews, and documentation. The validity test was done by using the triangulation technique. The result of this research was analyzed using Polya's problem-solving indicator with a percentage of 55.98% in the